Pemanfaatan Sumber Daya Alam Yang Berkelanjutan: Tantangan Dalam Tata Kelola Industri Pariwisata Yang Berbasis Kearifan Lokal - Wijaya, I Ketut Kasta Arya (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2024)
This paper will describe and analyze the potential of the use of natural resources in tourism development, areas that have beautiful natural resources and are still naturally one of the tourist destinations. The use of natural resources in the tourism industry has become a trend today. Thus, there needs to be governance that regulates how the utilization of natural resources as one in the tourism industry. In sustainable development there is a balance that must be done by the parties both the government, business actors and the community in building the tourism industry. The utilization of natural resources for the tourism industry is as wise as possible not to damage the environment but can contribute economically to the increasing economy of the local community. On the other hand, the local community still has a responsibility in maintaining its environment. So, there is a harmonious relationship between the environment (natural resources), local communities, and economic improvement.